1998
DOI: 10.1037/0893-164x.12.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a smoking timeline follow-back interview.

Abstract: Smokers with past major depressive disorder participating in a smoking cessation treatment study were interviewed at 6, 26, and 29 weeks postquit to retrospectively assess their smoking behavior using the timeline follow-back (TLFB) method. Participants also completed calendars by self-monitoring the number of cigarettes smoked each day for two 4-week periods over the 26-week follow-up. The 3-and 20-week test-retest reliabilities of the smoking TLFB interview were high. Agreement between participants' daily mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
381
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(386 citation statements)
references
References 27 publications
2
381
2
Order By: Relevance
“…25 To assess smoking status, telephone interviews were conducted at the end of treatment (EOT, 8 weeks following the TQD) and at 6-month follow-up (6 months following the TQD) using a standard timeline follow-back method. 48 Participants who reported complete abstinence (not even a puff of a cigarette) for at least the 7 days prior to the assessment were asked to complete an in-person visit for biochemical verification of abstinence.…”
Section: Study Design and Treatment Proceduresmentioning
confidence: 99%
“…25 To assess smoking status, telephone interviews were conducted at the end of treatment (EOT, 8 weeks following the TQD) and at 6-month follow-up (6 months following the TQD) using a standard timeline follow-back method. 48 Participants who reported complete abstinence (not even a puff of a cigarette) for at least the 7 days prior to the assessment were asked to complete an in-person visit for biochemical verification of abstinence.…”
Section: Study Design and Treatment Proceduresmentioning
confidence: 99%
“…Self-report data on smoking status were obtained at EOT and 6-month followup, using a validated timeline follow-back method. 21 Participants who reported complete abstinence (not even a puff of a cigarette) for at least the 7 days prior to the assessment were asked to complete an in-person visit for biochemical verification of abstinence using exhaled carbon monoxide (CO) reading (cotinine verification was not used because the treatments contained nicotine).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Specifically, baseline TLFB data were gathered for the 30 days prior to their first screening session and at all weekly appointments individuals were verbally asked to indicate the number of cigarettes they consumed each day for the preceding week. The TLFB has been shown to be a reliable and valid method of assessment of smoking behavior (Brown et al, 1998), and it has been shown to have good convergence with the biochemical markers CO and cotinine (Brandon, Copeland, & Saper, 1995).Smoking status was biochemically verified by measuring CO using a Vitalograph BreathCO monitor (Lenexa, KS), with readings of 10 ppm or greater coded as current smoking (SRNT Subcommittee on Biochemical Verification, 2002). This biomarker is adequate for the assessment of smoking as "any specimen in which the biomarker can be measured is suitable for determining smoking status" (SRNT Subcommittee on Biochemical Verification, 2002, p. 150).…”
mentioning
confidence: 99%
“…The TLFB has also been evaluated as a measure of past illicit drug use and tobacco smoking, and it has been shown to have adequate reliability and validity with these substances as well (Brown et al, 1998;Fals-Stewart, O'Farrell, Freitas, McFarlin, & Rutigliano, 2000;Hersh, Mulgrew, Van Kirk, & Kranzler, 1999).…”
mentioning
confidence: 99%